The "Teaching Mathematics and Computer Science" Journal logo's mathematical background - Oláh-Gál, Róbert; Salamon, Júlia (Teaching Mathematics and Computer Science, 2005)
In the present contribution we give an elementary technology for drawing the geodesics, paracycles and hypercycles on the pseudosphere.